2020
DOI: 10.1093/jhps/hnz075
|View full text |Cite
|
Sign up to set email alerts
|

Conservative management acutely improves functional movement and clinical outcomes in patients with pre-arthritic hip pain

Abstract: Conservative management for individuals with pre-arthritic hip pain is commonly prescribed prior to consideration of surgical management. The purpose of this study is to determine if patients with pre-arthritic hip pain will improve their functional movement control and clinical outcome measures following the implementation of physical therapy and a home-exercise programme. Information was retrospectively collected on consecutive patients and included: demographics, diagnosis, initial and follow-up evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…A classification-based treatment plan can be developed according the evaluation algorithm in conjunction with identified impairments. Interventions should be directed at a prioritized problem list that looks to address deficits in strength, ROM, flexibility and neuromuscular control, while considering biomechanical abnormalities [ 8 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A classification-based treatment plan can be developed according the evaluation algorithm in conjunction with identified impairments. Interventions should be directed at a prioritized problem list that looks to address deficits in strength, ROM, flexibility and neuromuscular control, while considering biomechanical abnormalities [ 8 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Strengthening activities for the muscles of the hip and lumbosacral spine may improve weakness and muscle imbalance. Exercises directed at improving neuromuscular control may help compensate for the boney deformities [ 13 ]. Therapeutic interventions need to be implemented with consideration for movements that provoke symptoms and should be executed in a pain-free manner that does not create additional joint irritation [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In combination, these previous studies demonstrate a need for further research into SLS squat performance in patients with FAIS. 11,12,18,24 Specifically for FAIS, it is important to determine the modifiable factors related to squat performance, such as hip biomechanics, muscle strength, and pain, as well as factors to identify how related nonmodifiable factors, such as bony morphology, are associated with this performance.…”
mentioning
confidence: 99%
“…Further support of this "top-down" approach to assessing SLST performance can be seen in intervention studies in which treatments targeting proximal muscle function have been shown to improve SLST performance. 1,60,61 These factors indicate that the evidence-based SLST protocol used in the current study and commonly implemented in the clinic may best be used to assess proximal, rather than distal, contributors to functional movement of the lower extremity kinetic chain. Furthermore, the results suggest that clinical screening of hip abductor strength by manual muscle test and Trendelenberg test is not adequate to detect a dysfunction that may result in MKD during the SLST.…”
Section: Discussionmentioning
confidence: 98%
“…The SLST is commonly used for injury prevention screening and physical rehabilitation evaluation. The test has been applied to individuals with non-arthritic hip pain, 1 patellofemoral pain syndrome, [2][3][4][5][6] knee osteoarthritis, 7 and anterior cruciate ligament (ACL) reconstruction. 8,9 Excessive medial knee deviation (MKD) during the eccentric phase of the squat is a common finding 10,11 and is used as a marker of aberrant movement patterns in both visual rating scales [12][13][14][15][16] and kinematic measurements.…”
Section: Introductionmentioning
confidence: 99%